KIR-HLA and maternal-infant HIV-1 transmission in sub-Saharan Africa. - Maria Paximadis; Gregory Minevich; Robert Winchester; Diana B Schramm; Glenda E Gray; Gayle G Sherman; Ashraf H Coovadia; Louise Kuhn; Caroline T Tiemessen (PLoS ONE)
Numerous studies have suggested a role for natural killer (NK) cells in attenuation of HIV-1 disease progression via recognition by killer-cell immunoglobulin-like receptors (KIRs) of specific HLA class I molecules. The role of KIR and HLA class I has not been addressed in the context of maternal-infant HIV-1 transmission. KIR and HLA class I B and C genes from 224 HIV-1-infected mothers and 222 infants (72 infected and 150 uninfected) from South Africa were characterized. Although a number of significant associations were determined in both the total group and in the nevirapine (NVP) exposed group, the most significant findings involved KIR2DL2 and KIR2DL3 and HLA-C. KIR2DL2/KIR2DL3 was underrepresented in intrapartum (IP)-transmitting mothers compared to non-transmitting (NT) mothers (P = 0.008) and remained significant (P = 0.036) after correction for maternal viral load (MVL). Homozygosity for KIR2DL3 alone and in combination with HLA-C allotype heterozygosity (C1C2) was elevated in IP-transmitting mothers compared to NT mothers (P = 0.034 and P = 0.01 respectively), and after MVL correction (P = 0.033 and P = 0.027, respectively). In infants, KIR2DL3 in combination with its HLA-C1 ligand (C1) as well as homozygosity for KIR2DL3 with C1C2, were both found to be underrepresented in infected infants compared to exposed uninfected infants in the total group (P = 0.06 and P = 0.038, respectively) and in the sub-group of infants whose mothers received NVP (P = 0.007 and P = 0.03, respectively). These associations were stronger post MVL adjustment (total group: P = 0.02 and P = 0.009, respectively; NVP group: P = 0.004 and P = 0.02, respectively). Upon stratification according to low and high MVL, all significant associations fell within the low MVL group, suggesting that with low viral load, the effects of genotype can be more easily detected. In conclusion this study has identified a number of significant associations that suggest an important role for NK cells in maternal-to-infant HIV-1 transmission.